2021
DOI: 10.29359/bjhpa.13.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Static balance and proprioception evaluation in deaf national basketball players

Abstract: Background: ‪Because of the proximity of anatomical structures involved in auditory and vestibular functions, complications concerning the inner ear may lead to problems involving both systems. This study investigated whether static balance and knee proprioception in deaf basketball players are different from those in individuals with normal hearing. Material and methods: ‪12 deaf national basketball players and 13 individuals with normal hearing were included. Static balance was evaluated using the Biodex-Bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In three studies with fourteen conditions, balance control of individuals with HI who participated in sports versus individuals with hearing was assessed (Farahani et al, 2013;Güzel et al, 2016;Cobanoglu et al, 2021]. The present meta-analysis on these studies showed that individuals with HI who participated in sports had a weaker balance than individuals with hearing.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In three studies with fourteen conditions, balance control of individuals with HI who participated in sports versus individuals with hearing was assessed (Farahani et al, 2013;Güzel et al, 2016;Cobanoglu et al, 2021]. The present meta-analysis on these studies showed that individuals with HI who participated in sports had a weaker balance than individuals with hearing.…”
Section: Discussionmentioning
confidence: 72%
“…The balance control of individuals with HI who participated in sports versus individuals with hearing was assessed in three studies with fourteen conditions [Farahani et al, 2013;Güzel et al, 2016;Cobanoglu et al, 2021]. Of these fourteen conditions, the I 2 overall index was equal to 89.29%, indicating that there was high heterogeneity between the fourteen conditions.…”
Section: Balance Control Of Individuals With Hi Who Participated In S...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ample research has been conducted to identify sources of referees' bias, and to reveal how accuracy of officiating can be improved ( Dohmen and Sauermann, 2016 ; Morgulev et al, 2018 ; Schweizer et al, 2013 ; Spencer et al, 2020 ). Contributing factors that have been found to assist referees in their DM processes include physical fitness ( Helsen and Bultynck, 2004 ; Leicht, 2008 ), perceptual ability ( Helsen and Bultynck, 2004 ; Kittel et al, 2019 ; Cobanoglu et al, 2021 ), mental ability ( Anshel et al, 2014 ; Castillo et al, 2017 ), visual attention ( Pietraszewski et al, 2014 ; Spitz et al, 2018 ), rules knowledge, and game management ( Mascarenhas et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Different criteria have been used to evaluate the uniqueness of WB determinants and the classification system based on short-term efforts in WB. Anaerobic power in WB has been examined by studying athletes’ anaerobic performance in a variety of laboratory tests ( de Lira et al, 2010 ; Hutzler et al, 1998 ; Molik et al, 2013 ; Molik et al, 2010 ) or field-based tests ( Cavedon et al, 2015 ; Cobanoglu et al, 2021 ; Doyle et al, 2004 ; Gil et al, 2015 ; Molik et al, 2013 ; Tachibana et al, 2019 ) and compared to players’ classification. Sprint tests (5m, 20m), agility tests (T-test, figure eight with the ball) and ball passes (one- or two-handed ball pass tests) have often been used.…”
Section: Introductionmentioning
confidence: 99%